Association between dietary consumption patterns and the development of adolescent overnutrition in eastern Ethiopia: new perspectives - Gedamu, Fikerte; Dagne, Imam; Oumer, Abdu (Frontiers in Nutrition, 2023)
Background: Overnutrition among adolescents is becoming a major public health concern, with all the adverse consequences associated with unhealthy eating behaviors. Hence, clear evidence linking dietary consumption with the risk of overnutrition is crucial for targeted dietary recommendations using a robust statistical approach. This study assessed the link between dietary consumption patterns and the risks of overnutrition among adolescents in Ethiopia.Method: A community-based survey was conducted on a random sample of 510 adolescents selected using a stratified random sampling proportional allocation. Dietary consumption was captured using a validated and contextualized 80-item food frequency questionnaire over the past month through a face-to-face interview. Weight and height were measured under a standard procedure. Body Mass Index for Age Z-score (BAZ) was calculated, and BAZ above +1 was considered overnutrition. The frequency measures were standardized into daily equivalents, and dietary patterns were derived using exploratory factor analysis after checking for assumptions. A bivariable and multivariable binary logistic regression model was fitted with an odds ratio and 95% confidence intervals.Results: A total of 510 participants were enrolled. Four major dietary patterns ("cereals, energy, and discretionary calory," "fat, oil, and milk groups," "proteins and vegetables," and "fruits"), explaining 66.6% of the total variation, were identified. The overall prevalence of overnutrition was 29.0% (27-31%), where 22.5% and 6.5% were overweight and obese, respectively. Physical